Emissions and Exposures Associated with the Use of an Inconel Powder during Directed Energy Deposition Additive Manufacturing - van Ree, Marelizé; du Preez, Sonette; du Plessis, Johan L. (International journal of environmental research and public health, 2023)
Additive manufacturing (AM) has been linked to potential exposure-related health risks, however, there is a paucity of sufficient research. This study aimed to supply information regarding emissions and exposure during directed energy deposition (DED) AM using inconel 718, with the main constituents being nickel, chromium, and cobalt. By using standardized occupational hygiene methods, the measurement strategy consisted of a combined approach, including powder characterization, particle emission monitoring, and personal exposure monitoring of AM operators. Powder characterization of virgin and used powder indicated no significant difference in particle size, shape, or elemental composition. Particle number emissions ranged between 102 and 105 p/cm3 for submicron particles (<1 µm in size). There was no significant difference in the particle emission rate between the three phases of AM or the two types of DED machines (p > 0.05). The particle emission rate for submicron particles peaked at 2.8 × 109 p/min. Metals of concern to human health were detected during the AM process but were considerably lower than the relevant exposure limits. This study confirms particle emissions, predominantly in the submicron range, above the background concentration during DED AM and, although insignificant in terms of potential health effects, AM operators are exposed to detectable concentrations of the metal constituents of inconel.